2017
DOI: 10.21134/haaj.v17i1.265
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentos de evaluación del uso problemático del teléfono móvil/Smartphone

Abstract: ResumenThe Smartphone has become an object indispensable for Tras el análisis, se observa una falta evidente de fundamento teórico que sustente este tipo de trastorno conductual, ya que no existe consenso en su inclusión dentro de una taxonomía determinada y cada instrumento utiliza criterios diagnósticos provenientes de trastornos distintos del DSM-V, lo que dificulta todavía más la comparativa entre las escalas.Los futuros estudios deben ir encaminados a establecer criterios diagnósticos propios al uso probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Additionally, authors such as Billieux consider the "problematic mobile phones' use" (PMPU) as an inability to regulate the use of mobile phones, which eventually leads to negative consequences in daily life [24]. Studies carried out in Spain find percentages of people with PMPU that vary between 7.99% and 12.5% using different scales [25]. To this end, three different ways were established to define the problematic use of the mobile with its three respective behavior patterns: addictive pattern, antisocial pattern, and risk use pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, authors such as Billieux consider the "problematic mobile phones' use" (PMPU) as an inability to regulate the use of mobile phones, which eventually leads to negative consequences in daily life [24]. Studies carried out in Spain find percentages of people with PMPU that vary between 7.99% and 12.5% using different scales [25]. To this end, three different ways were established to define the problematic use of the mobile with its three respective behavior patterns: addictive pattern, antisocial pattern, and risk use pattern.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the objective of establishing diagnostic criteria for behavioral addictions, it is also necessary to develop reliable and valid measures of these behaviors and regularly assess their psychometric properties, especially because the technological and social trends related to these behaviors change rapidly [8]. Diverse authors designed several instruments to evaluate this problematic use of the mobile phone [25], and even different diagnostic criteria were established for smartphone addiction [27].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reasonably well-established that young people feel the need to be continually connected to their mobile phones, a solid theoretical basis cannot be found that supports this disorder; neither is there unanimity in the established evaluation instruments [40]. In consideration of this, and bearing in mind that it has been presented by [9] that, up until the date of writing, little empirical evidence exists relating problematic mobile phone use with potential behavioural addictions, the present work proposes the following objectives: (a) To determine the levels of nomophobia (low, medium or high) within a sample of students of Education Sciences, according to their individual scale ratings and the characteristics of the sample being analysed; (b) to examine whether a cross-tabulation of different demographic variables relating to students (gender, age range, degree title and degree year) shows statistically significant differences with regards to the variable describing levels of nomophobia and (c) to check whether the demographic variables previously discussed, together with the variable describing the nomophobia level, produce any type of correspondence that can generate a student profile describing a higher or lower level of nomophobia.…”
Section: Introductionmentioning
confidence: 99%
“…Authors such as Billieux consider the "problematic mobile phones' use" (PMPU) as an inability to regulate the use of mobile phones, which eventually leads to negative consequences in daily life [12]. Studies carried out in Spain find values of PMPU that oscillate between 7.99% and 12.5% using different scales [13]. Three different ways have been established to define the problematic use of the mobile with its three respective behavior patterns: addictive pattern, antisocial pattern and risk use pattern.…”
Section: Introductionmentioning
confidence: 99%